BASIC LIFE SKILLS DALAM PEMBELAJARAN DI SEKOLAH DASAR - Muhammad Saufi (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
Basic life skills is the ability and knowledge of a person to dare to face the problems of life and proactively seek and find solutions so that they are finally able to overcome them with the ability to interact and adapt to others, decision-making skills, problem solving, critical thinking, creative thinking, effective communication, building relationships between individuals, self-awareness, empathy, emotional addressing, and stress relief Basic Life Skills is closely related to the ability of a human being as a personal or social creature in the future. Educational life skills in elementary school are focused on General Life Skills (GLS) which include self awareness or self awareness, rational thinking skills and social skills. It is based on the principle that the GLS is the foundation of life prowess that will be needed to learn the next life prowess and even to plunge into everyday life.